Penerapan Intervensi Pemberdayaan Teman Sebaya (PERSEBAYA) untuk Mengatasi Perilaku Mencederai Diri pada Remaja di SMP Negeri 21 Kabupaten Tanjung Jabung Timur, Jambi - Nasution, Riska Amalya; Meinarisa, Meinarisa; Kamariyah, Kamariyah; Mawarti, Indah; Falani, Ilham (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Adolescent is a period of transition to adulthood. At this age, adolescents are prone to experiencing mental health problems, one of which is self-injurious behavior. Adolescents who have self-injurious behavior need social and emotional support from various parties such as parents, health workers, schools, teachers and peers. Peer empowerment helps to train adolescents to recognize their potential, learn to be responsible, lead, and other positive activities that can overcome the problems of adolescents who have self-injurious behavior. The problems encountered in partner groups are; there is no use of peers to solve problems in adolescents, the school has never held special education about PERSEBAYA, and the incidence of students dropping out of school. This community service activity was carried out at Junior High School 21 Tanjung Jabung Timur Regency as a health partner. The purpose of this service is to carry out prevention efforts in adolescents by providing PERSEBAYA intervention. The method used is an experimental method where adolescents are given treatment in the form of PERSEBAYA intervention. The results of this service are expected that adolescents recognize the growth and development that must be achieved by adolescents and are able to control the desire to injure themselves